Navigating the Entrepreneurial Journey: Strategies for Effective Learning Management in Fostering Student Entrepreneurial Talent - Rahmatullah, Rozi; Murniati, Murniati; Usman, Nasir (JURNAL AL-TANZIM, 2024)
This research analyzes the management of student entrepreneurial talent development at State Vocational Schools in Banda Aceh City. The research uses a qualitative case study type approach. Data collection techniques were carried out through observation, interviews, and documentation studies. Research at SMK Negeri 1, SMK Negeri 2, and SMK Negeri 3 revealed several main findings. First, entrepreneurship learning planning in the three schools is carried out effectively with different strategies and focuses. Second, the implementation of entrepreneurship education shows a good approach, where each school adopts methods according to its context, cultivating various skills in its graduates. Third, despite differences in learning management, the process still follows standard guidelines and uses learning tools according to the Independent Curriculum. Obstacles included a need for more student understanding, motivation, and practicum costs. The solution includes competency tests, mid-semester exams, market days, and project assignments tailored to student competencies. Thus, vocational schools in Banda Aceh City aim to equip students with entrepreneurial intelligence and practical skills for business success.